Synthesis of Wax Esters From Palm Kernel Oil Catalyzed by Lipase - Erin Ryantin Gunawan; Dedy Suhendra (Institut Teknologi Bandung, 2008)
The lipase catalyzed reaction of wax esters synthesis using palm kernel oil and long chain alcohol (oleyl alcohol) assubstrates and lipase lipozim as catalist was carried out. The effects of various reaction parameters such as reactiontime, temperature, amount of enzyme, molar ratio of substrates and various organic solvents were investigated. Theoptimum reaction condition for wax ester synthesis is a mixture of palm kernel oil and oleyl alcohol with molar ratio of(3:1), with 1.5% (w/v) lipozyme, at 40 oC for 7-10h, and with hexane as the best solvent. Percentage yields of wax estersobtained at these optimum reaction conditions was 84.4 Â± 2.85 %.